2016
DOI: 10.1149/2.0071705jes
|View full text |Cite
|
Sign up to set email alerts
|

Review—Where Is Dielectrophoresis (DEP) Going?

Abstract: A guide is offered to new researchers (and their supervisors) of the most promising topics to explore in market-driven or curiositydriven dielectrophoresis (DEP) research. Based on an analysis of publications since 2000, contributions from electronic engineers and materials scientists are likely to be maintained, with increasing emphasis on the development of DEP-based protocols for chemical and biochemical analyses that involve nanoparticles. Two modes of DEP are likely to dominate, namely metal-electrode bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
112
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(114 citation statements)
references
References 60 publications
2
112
0
Order By: Relevance
“…1, where the highest electric field region is located at the tips of the curved microelectrodes. Pearl-chaining is also described as mutual DEP [28] and occurs when the electrostatic interactions between polarized cells rebalance their electrical potential energies [29]. MDA-MB-231 cells in 1% DMEM solution experience positive DEP which is confirmed by the responses of Cell A and B in Figs.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…1, where the highest electric field region is located at the tips of the curved microelectrodes. Pearl-chaining is also described as mutual DEP [28] and occurs when the electrostatic interactions between polarized cells rebalance their electrical potential energies [29]. MDA-MB-231 cells in 1% DMEM solution experience positive DEP which is confirmed by the responses of Cell A and B in Figs.…”
Section: Discussionmentioning
confidence: 77%
“…3, cell C is already in contact with cell D and rotates towards cell E to form a chain-like formation which is known as pearl chaining [27]. Pearl-chaining is also described as mutual DEP [28] and occurs when the electrostatic interactions between polarized cells rebalance their electrical potential energies [29]. Cells naturally have repulsive forces between opposing membrane surfaces which are known as electrostatic repulsion and hydration repulsive forces [30].…”
Section: Discussionmentioning
confidence: 99%
“…DEP spectra were obtained from each experiment, and were then modelled to extract the dielectric properties. The modelling was performed by varying parameters to find the best fit (highest Pearson correlation coefficient) between the data points and a model of the composite dielectric properties of a shelled particle , as related through a mathematical operation called the Clausius‐Mossotti factor . This is frequency dependent, such that measuring the DEP behaviour at different frequencies and fitting a model to these points allows the estimation of the electrical properties of the cells.…”
Section: Methodsmentioning
confidence: 99%
“…In the following years, many variants of this separation technology were published, presenting multiple separation outputs [22], vertical electrodes [23] and more, and several cell types used; several excellent review can be found describing both technology and applications elsewhere (e.g., [24]). However, this period did not see the advancement of DEP separation outside of engineering departments; it could be argued that there was a disconnection between the technology providers and the ultimate end users.…”
Section: The Path To Commercializationmentioning
confidence: 99%